Leaf Pigment, Phenolic Content, and Production of Green Shallot of Five Different Shallot Varieties - Putri, Fiadini; Aziz, Sandra Arifin; Andarwulan, Nuri; Melati, Maya; Suwarto, Suwarto (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2021)
Five shallot varieties namely ‘Bauji’, ‘Bantaeng’, ‘Tuk Tuk’, ‘Rubaru’, and ‘Palasa’ were examined for their leaf pigment, total phenolic content, leaf tissue nutrient analysis, and green shallot production. The experiment was conducted in in Cikabayan greenhouse, IPB University, Dermaga, Bogor, arranged in a randomized complete block design with single factor (variety) and three replications. The observations were carried out three times in the maximum vegetative period, consisting of 20, 30, and 40 days after planting. The result showed that ‘Palasa’ had the highest leaf pigment content, such as chlorophyll a, chlorophyll b, total chlorophyll, and carotenoid, while the anthocyanin content fluctuated between the varieties and observation times. ‘Palasa’ also had the highest sulfur content in the leaf tissues. On the contrary, ‘Palasa’ had the lowest production compared to other the varieties. Meanwhile, ‘Bantaeng’ had the highest green shallot production, total nitrogen, and total phosphorus content in the leaf tissues. Total phenolic content fluctuated in the five varieties and observation times. The highest total phenolic content was in ‘Tuk Tuk’, observed 20 days after planting. The principal component analysis (PCA) showed that the five shallot varieties formed three clusters. The first was ‘Palasa’, the second cluster was ‘Bauji’, ‘Tuk Tuk’, and ‘Rubaru’, while the third cluster was ‘Bantaeng’. ‘Palasa’ had the highest content of leaf pigment, while Bantaeng had the highest leaf production. Leaf pigment and total phenolic content changed along with the increasing plant age in all varieties.